Guidance and control system using constrained adaptive backstepping method for space transportation. (September 2016) - Abe, Akio; Iwamoto, Kohei; Okafuji, Yuki; Kanehira, Hayato; Sasa, Shuichi
This study presents a new guidance and control system using a constrained adaptive backstepping method for a space transportation system. In this method, the effects of input saturations by actuator dynamics (e.g. magnitude, rate and bandwidth) are considered to introduce the compensators on the basis of pseudo control hedging. The stability of the proposed entire system is guaranteed by the Lyapunov' stability theorem. To confirm the realization and robustness of the proposed system, Monte Carlo simulations (MCSs) were performed. In addition, to obtain optimized control performance, a parameter optimization algorithm combined with the MCSs was introduced. Finally, automatic landing simulations using the six degrees-of-freedom nonlinear flight simulation model of the NASA's Space Shuttle Orbiter were performed to verify the effectiveness of the proposed technique.